NEW DISTRIBUTIONAL RECORD OF ASIAN OPENBILL Anastomus oscitans IN SUMATRA, INDONESIA: AN UPDATE TO AMINUDDIN et al. (2020) - Syahras Fathin Aminuddin; Chairunas Adha Putra; Prayitno Geonarto; Taufik Ardiansyah; Tedi Setiadi (Masyarakat Zoologi Indonesia, 2022)
The occurrence of Asian Openbill Anastomus oscitans has been confirmed in Indonesia, specifically in the Sumatra region. Its first two confirmed observations were in December 2019 at Abang Island (Riau Islands) and in September 2020 at Bagan Percut (North Sumatra). We conducted more observations to record its presence in the eastern side of Sumatra Island for several months in 2020. We observed Asian Openbill at three new locations in Riau province. There are many aspects from the occurrences of these birds in the Sumatra region that need to be investigated, especially to picture its current distribution and status, ecological requirement, and potential role as rice pest control.